Citation is Inescapable: Enhancing Students’ Referencing Skills with an Online APA Escape Room - Doherty, Tiffany (Canadian Perspectives on Academic Integrity, 2023)
Referencing is an important component to upholding academic integrity in university writing, but it can be difficult to teach in a way that really “sticks” for students. Students (and, sometimes, educators) often perceive referencing as boring and tedious because of the seemingly-countless rules involved with each unique style. Even when offered foundational instruction in a referencing style, students often struggle to independently solve citation challenges that require the confidence to apply specific rules and a degree of personal judgment. Looking to enhance students’ proficiency and confidence with referencing, a team of three Learning Strategists co-developed an online escape room to engage students in an active and fun way as they collaborate on problem-solving scenarios for APA Style. In this workshop, participants will learn why and how the escape room was developed, try out an abridged version of the escape room, and discuss how this and other game-based approaches to teaching could be used to facilitate academic integrity learning.